2022
DOI: 10.3390/v14050995
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Comparison of Novel Bovine Leukemia Virus (BLV) Integration Sites between B-Cell Lymphoma Lines BLSC-KU1 and BLSC-KU17 Using the Viral DNA Capture High-Throughput Sequencing Method

Abstract: Bovine leukemia virus (BLV) infects cattle and integrates into host DNA, causing enzootic bovine leukosis (EBL), an aggressive B-cell lymphoma. Here, we developed a novel proviral DNA-capture sequencing (proviral DNA-capture-seq) method investigating BLV proviral integration in two B-cell lymphoma lines, BLSC-KU1 and BLSC-KU17, derived from BLV-infected cattle with EBL. We designed BLV-specific biotinylated probes to capture the provirus genome and enrich libraries for next-generation sequencing. Validation sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 58 publications
0
12
1
Order By: Relevance
“…We clarified the BLV integration sites from Stages I-III using BLV proviral DNA-capture-seq, which is a targetenrichment high-throughput sequencing system for characterization of BLV integration sites [14]. The DNAs molecules were fragmented to an average length of approximately 600 bp to generate DNA libraries.…”
Section: Results Of Blv Proviral Dna-capture-seqmentioning
confidence: 99%
See 4 more Smart Citations
“…We clarified the BLV integration sites from Stages I-III using BLV proviral DNA-capture-seq, which is a targetenrichment high-throughput sequencing system for characterization of BLV integration sites [14]. The DNAs molecules were fragmented to an average length of approximately 600 bp to generate DNA libraries.…”
Section: Results Of Blv Proviral Dna-capture-seqmentioning
confidence: 99%
“…In this study, we monitored the sequential alternation of BLV integration sites in a BLV naturally-infected Holstein cow from Stages I to III, using proviral DNA-captureseq previously developed by us [14]. In this study, we identified 16 distinct proviral integration sites in Stage I.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations